2014
DOI: 10.1016/j.yexcr.2014.02.007
|View full text |Cite
|
Sign up to set email alerts
|

The tick tock of odontogenesis

Abstract: Although a big deal of dental research is being focused to the understanding of early stages of tooth development, a huge gap exist on our knowledge on how the dental hard tissues are formed and how this process is controlled daily in order to produce very complex and diverse tooth shapes adapted for specific functions. Emerging evidence suggests that clock genes, a family of genes that controls circadian functions within our bodies, regulate also dental mineralized tissues formation. Enamel formation, for exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 46 publications
0
30
0
2
Order By: Relevance
“…Local interneurons mainly contact the neurosensory odontoblast (Farahani et al, ). As such, modulation of the synthetic rhythm (Zheng et al, ) or the sensory activity of odontoblasts based on the inhibitory input from local inhibitory interneurons is a plausible outcome. The proposed modulation of odontoblastic activity may occur in a manner akin to regulation of retinal photoreceptors by resident interneurons that lead to contrast enhancement (Chapot, Euler, & Schubert, ).…”
Section: Discussionmentioning
confidence: 99%
“…Local interneurons mainly contact the neurosensory odontoblast (Farahani et al, ). As such, modulation of the synthetic rhythm (Zheng et al, ) or the sensory activity of odontoblasts based on the inhibitory input from local inhibitory interneurons is a plausible outcome. The proposed modulation of odontoblastic activity may occur in a manner akin to regulation of retinal photoreceptors by resident interneurons that lead to contrast enhancement (Chapot, Euler, & Schubert, ).…”
Section: Discussionmentioning
confidence: 99%
“…Deletion experiments by Ohtsuka‐Isoya et al () in rats later suggested that the circadian rhythm of dentinogenesis is controlled via the suprachiasmatic nucleus in the diencephalon. Recently, it was demonstrated that circadian clock genes are also expressed in mouse molars and it has been suggested that these genes are involved in enamel and dentine matrix secretion and mineralization (Zheng et al, ). In appropriately stained tooth sections, daily incremental growth markings are visible already in the predentine (Dean, ), in line with the assumed regulation of matrix secretion by clock genes.…”
Section: Introductionmentioning
confidence: 99%
“…12,16 Calcium acts as the second messenger which regulates cellular activities and it has been linked to some signaling pathways during tooth development. 17,18 The calcium ions generated from nano calcium that were fed to Sprague Dawley then spread in the body through blood circulation and helped the mineralization in dental hard tissue. According to a previous study, the number of calcium ions released by nano calcium can be twice or three times higher than those by micro calcium.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium is known as the second messenger which regulates cellular activities and has been linked to some signaling pathways during tooth development. 17,18 The formation of enamel requires large quantities of calcium ions which travel through extracellular and transcellular routes. 12,19 In the body there are a number of possible sources for calcium that will mineralize enamel matrix.…”
Section: Discussionmentioning
confidence: 99%